Innovation Facilitated by Universities: Balancing Enterprise and Regional Demands. (7th March 2022) - Wang, Qi; Zhang, Ling-Na; Lian, Qi
Abstract : Innovation constitutes an important output of education. With the differences in the two-dimensional cooperation between universities, the government, and enterprises in the mode featuring "triple helix" as a starting point, this article has compared the features of the influence of differences in the quality of higher education on enterprise and regional innovation by adopting the data of listed companies and provincial-level macro-statistical data from 2013 to 2020 to construct the count panel data model. The research has proved that the "inverted U" feature is presented between the range of quality among universities and the level of innovation output. However, the coefficient of the differences in quality between universities in relation to the optimal innovation output of enterprises is higher than that of regional innovation output. That is to say, differences are existent in the differences in the path of the influence of the differences in quality between universities with respect to entrepreneurship and national innovation. To some extent, this research result explains the reason why the country has cultivated a large number of talents but is still faced with the situation characterized by the lack of talents related to the so-called crucial technologies. Therefore, on the basis of guaranteeing the basic operation rules of higher education, it is necessary for the third-party institutions to provide differentiated higher education information for enterprises and countries (regions) to realize the unity of the classification of schools in education and the signal of market-element allocation. Moreover, university alliances should be established so that the innovation demands based on enterprises and regions can be met through the transmission of information between universities so as to prevent universities from becoming tools for helping enterprises maximize their profits or for the government to pursue educational achievements.